2005
DOI: 10.1063/1.1935045
|View full text |Cite
|
Sign up to set email alerts
|

Space-charge-limited current involving carrier injection into impurity bands of high-k insulators

Abstract: Photoelectrical measurements have shown that the current flow through La2Hf2O7 and LaAlO3 high-k insulator layers deposited on silicon takes place via impurity channels. A space charge limited current is evidenced, for different insulator thicknesses and temperatures, by the square law dependence of current versus voltage. The analysis demonstrates that this space charge limited (SCL) current in thin insulator films can be explained only by the presence of impurity channels situated near the Fermi level of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…where ε i (ε r ε 0 ) is the permittivity of the oxide and μ is the mobility, d is the thickness of oxide, θ is the ratio of free to shallow trapped charge. Goldenblum et al [25] reported that a SCL current can be evidenced if the μθ factor is very small as a result of the high trap level occupancy and the low carrier mobility. By fitting the experimental current densities (J) with equation ( 5), we found the μθ product values ranging from 10 −11 to 10 −9 cm 2 V s −1 , i.e.…”
Section: Resultsmentioning
confidence: 99%
“…where ε i (ε r ε 0 ) is the permittivity of the oxide and μ is the mobility, d is the thickness of oxide, θ is the ratio of free to shallow trapped charge. Goldenblum et al [25] reported that a SCL current can be evidenced if the μθ factor is very small as a result of the high trap level occupancy and the low carrier mobility. By fitting the experimental current densities (J) with equation ( 5), we found the μθ product values ranging from 10 −11 to 10 −9 cm 2 V s −1 , i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Together with the results from photocurrent measurements which show a clear photosignal generated in Si, this proves that part of the source-drain current flows through a conduction channel in Si, after it has been injected transversally in the heterostructure through the SiO 2 insulator. It was shown in [18] that carrier injection through thin film insulators via impurity bands is a possible mechanism for carrier leakage in MOS structures. The inset in Fig.…”
Section: Field-effect On the Dark Currentmentioning
confidence: 99%